2019
DOI: 10.1108/ijdrbe-04-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and awareness of earthquake: the case of Dhaka

Abstract: Purpose Among the many studies about risk perception, only a few deal with Bangladesh. Paul and Bhuiyan’s (2010) study has shown the earthquake-preparedness level of residents of Dhaka, but there are some biases in the data collection. This paper aims to examine the seismic-risk perception and the level of knowledge on earthquake and preparedness among the residents of Dhaka. Design/methodology/approach A questionnaire was developed, and data collection was undertaken through home and sidewalk surveys. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…we found that middle-aged people in their 40 and 50s have the highest perception of risk. Education is also an important factor in perceived disaster risk, and the majority of respondents in this study had primary or secondary education, where educated respondents had significantly higher risk perceptions than uneducated ones, and our findings are consistent with those of Rahman (2019). A particular finding of this study is that respondents with primary education almost always live and work locally, are very familiar with their surroundings, and almost always live halfway up the mountain, whereas most respondents with secondary and post-secondary education chose to go out for work (Xu et al, 2020;Zhuang et al, 2020), are less familiar with the local geological environment than residents at home and have home addresses mostly near river valleys.…”
Section: Discussionsupporting
confidence: 89%
“…we found that middle-aged people in their 40 and 50s have the highest perception of risk. Education is also an important factor in perceived disaster risk, and the majority of respondents in this study had primary or secondary education, where educated respondents had significantly higher risk perceptions than uneducated ones, and our findings are consistent with those of Rahman (2019). A particular finding of this study is that respondents with primary education almost always live and work locally, are very familiar with their surroundings, and almost always live halfway up the mountain, whereas most respondents with secondary and post-secondary education chose to go out for work (Xu et al, 2020;Zhuang et al, 2020), are less familiar with the local geological environment than residents at home and have home addresses mostly near river valleys.…”
Section: Discussionsupporting
confidence: 89%
“…Risk perception causes people to worry and be upset, but ultimately causes little harm. In addition, risk perception is dependent on personal risk experience and risk history [14,15,28]. Therefore, for efficient disaster management, the individuals' sense of risk should be strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…Disaster risk perception refers to the perception of an individual's subjective risks for the occurrence of a disaster [14,15]. This scale was developed based on previous studies [12,13,19] and expert group consultation.…”
Section: Disaster Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies (Rana et al 2021;Rodriguez-Besteiro et al 2021), gender differences in the COVID-19 pandemic risk perception were analyzed, while in Rosi et al (2021) and in Kowalsky et al (2021), COVID-19 risk perceptions were related to age, considering the differences between youths and adults. Age was also considered as a variable of influence on disaster risk perception (Rahman 2019;Seyedin et al 2019). Eryılmaz Türkkan and Hırca (2021) examined the effect of sociodemographic characteristics on flood risk perception, finding a positive relationship between education and income levels and flood risk perception.…”
Section: Demographics Risk Perception and Trainingmentioning
confidence: 99%